Study of itaconic acid production by aspergillus terrus mjl05 strain with different variable (2010)
Título en español: Estudio de la producción de ácido itacónico con Aspergillus terreus de la cepa MJL05 con diferentes variables Abstract Itaconic acid (IA) production by Aspergillus terreus MJL05 strain was investigated in submerged batch fermentation in a stirred bioreactor to determine the effect of varying the nitrogen, phosphorous and carbon sources concentrations in the production medium. Glycerol, a biodiesel by-product was reported as an efficient substrate to achieve high itaconic acid productivities. This was used as the sole carbon source. The resulting C:N 18, N:P 10.8 and C:P 195 ratios were selected as the best and allowed to improve IA concentration from 11.0 to 27.6 g/l with a volumetric productivity of 0.192 g IA/l.h and a specific productivity 0.013 g IA/g biomass.h. Bioprocess yields, Yx:s 0.27 g d.w. biomass/g substrate; Yp:x 1.63 g IA/g d.w. biomass and Yp:s 0.44 g IA/g substrate, allowed to assume the feasibility of using this strain for IA production. Key words: Itaconic acid; Aspergillus terreus; glycerol. Resumen La producción de ácido itacónico (AI) con Aspergillus terreus MJL05 se realizó en fermentación sumergida en lote en un biorreactor agitado para estudiar el efecto de la variación de las concentraciones de nitrógeno, fósforo y carbono en el medio de producción. El glicerol, subproducto del biodiesel, fue reportado como un sustrato eficiente para obtener altas productividades de AI. Este fue utilizado como única fuente de carbono. Las relaciones entre nutrientes, C:N 18, N:P 10,8 y C:P 195 fueron seleccionadas como las mejores para aumentar la concentración de AI de 11,0 a 27,6 g/l con un a productividad volumétrica de 0,192 g IA/l.h, y una productividad específica de 0,013 g IA/g biomasa.h. Los rendimientos del bioproceso obtenidos fueron de Yx:s 0,27 g p.s. biomasa/g sustrato; Yp:x 1,63 g IA/g p.s. biomasa y Yp:s 0,44 g IA/g sustrato, lo que permite asumir la factibilidad de usar esta cepa para la producción de AI. Palabras clave: ácido itacónico; Aspergillus terreus; glicerol.